Evaluasi Kebijakan Surat Edaran NO. 2776/PB PDGI/III-3/2020 di Rumah Sakit Gigi Dan Mulut dan Klinik Di Kota Makassar - Nisa Musfirah; Samsualam; Andi Nurlinda (Program Pascasarjana Universitas Muslim Indonesia, 2021)
Backgorund: The SARS-Cov-2 pandemic had a negative impact on all aspects of health including dentists. Dentists are asked to conduct screening (screening) of all patients who will receive treatment. If it is known that a patient who is suspected of being infected with Covid-19 is immediately referred to the nearest hospital for further treatment. Therefore, based on the background of the problems that have been described, the researchers are interested in examining the extent of the policy evaluation of Circular No. 2776 / PB PDGI / III-3/2020 In Dental and Oral Hospitals and Clinics in Makassaar City. Research Methods: This research method is qualitative data collection by means of observation and in-depth interviews (in-depth interview) to evaluate Circular No. 2776 / PB PDGI / III-3/2020. Research Result: The results of this study describe the input, process, and output of the Circular No. 2776 / PB PDGI / III-3/2020 which includes human resources (dentists) on duty must be physically and mentally healthy, adequate facilities and infrastructure at hospitals and clinics, PDGI management cab. Makassar issued a policy for all dentists in Makassar not to practice except for emergency treatment. Conclusion : The conclusion of the study shows that the successful implementation of the policy is seen with each patient following all existing protocols in the hospital.